Variable Valve Timing / Rahmat Nizam Romzan, Mohd Hezrin Hashim and Norfazizi Razali - Romzan, Rahmat Nizam; Hashim, Mohd Hezrin; Razali, Norfazizi (Faculty of Mechanical Engineering, 2002)
The main objective of this thesis is to study the different types of Variable Valve Timing (WT) used by carmaker manufacturers. The other objective is to learn about the basic principal and the mechanisms use in VVT. In this thesis we make comparisons between the two well-known car largest manufacturers in the world TOYOTA and HONDA that uses Variable Valve Timing. From the different types of WT we will analyze and try to detect the weaknesses of the WT system if any. We will then come up with suggestions on the new W T system to achieve better engine performance as compared to the conventional WT. Aside from the above, we hope to also improve our computer skills during the writing up of the thesis where Microsoft words will be used. Cooperation skills and group teamwork will be further developed. Last but not least, most importantly, we will be able to enhance our knowledge in a new technology of W T and the entire concept related to the WT system.